TSH and cardiovascular risk factors: analysis in an overweight and obese euthyroid school population - Pajuelo-Ramírez, Jaime (2021)
Objective. To describe the level of thyroid stimulating hormone (TSH) and free plasma thyroxine (FT4) in school students with overweight and obesity; also determine the association between TSH and cardiovascular risk factors. Methods. 96 women schoolchildren, between 7 to 17 years old, euthyroid, were studied. Overweight BMI was defined as 85 to <95p and obesity ≥95p. Glucose, triglycerides, total cholesterol, high and low density cholesterol, TSH and FT4 were determined. To define the subgroups, a value of 75p of TSH was chosen. Results. Anthropometric variables and TSH was significantly higher among obese women, however, biochemical variables did not differ between groups. Those who were overweight and had a TSH> 75p had significantly higher waist circumference (WC) measurements, compared to the TSH <75p group, with no difference in the other variables. A positive and significantlinear association (p <0,001) was found between the TSH level and the z-BMI score (r = 0,37) and the WC (r = 0,51); there was no association between TSH and other cardiovascular risk factors. In the linear regression it was found that for each TSH unit increased, the z-BMI score increased by 0,25 and the WC by 2,25 cm adjusted for age, this finding being significant. Conclusion. TSH values were significantly higher in obese girls compared to overweight girls. Z-BMI score and waist circumference increase as TSH increases, regardless of age. No relationship was found between TSH levels and cholesterol, triglycerides and glucose levels.